Relationships between functional movement screen scores, maturation and physical performance in young soccer players - Lloyd, R. S.; Oliver, J. L.; Radnor, J. M.; Rhodes, B. C.; Faigenbaum, A. D.; Myer, G. D. (Journal of Sports Sciences, 2015)
The purpose of this study was to examine relationships between functional movement screen scores, maturation and physical performance in young soccer players. Thirty males (11-16 years) were assessed for maturation, functional movement screen scores and a range of physical performance tests (squat jump, reactive strength index protocol and reactive agility cut). Older players significantly outperformed younger participants in all tests (P < 0.05; effect sizes = 1.25-3.40). Deep overhead squat, in-line lunge, active straight leg raise and rotary stability test were significantly correlated to all performance tests. In-line lunge performance explained the greatest variance in reactive strength index (adjusted R2 = 47%) and reactive agility cut (adjusted R2 = 38%) performance, whilst maturation was the strongest predictor of squat jump performance (adjusted R2 = 46%). This study demonstrated that variation of physical performance in youth soccer players could be explained by a combination of both functional movement screen scores and maturation.